(untitled) (Heritage, 2026)
This paper examines the drawings of Radomir Paja Janković (1943–1994) as visual historical sources for the study of old Priština in the second half of the twentieth century. Starting from the biographical and artistic context of an artist who lived and worked in Priština, the paper analyzes his body of drawings as testimony to the urban space at the moment of its disappearance. Special attention is devoted to architectural motifs, compositional solutions, and drawing techniques that enable the reconstruction of the morphology of the old city center and the atmosphere of a traditional way of life. The drawings are considered in relation to earlier written sources, travelogues, and ethnographic records from the nineteenth century, which provide narrative descriptions of space and everyday life and which find a visual resonance in Janković’s work. In this way, the paper highlights the importance of fine art as a reliable visual source for the study of urban history, cultural memory, and the processes of disappearance of traditional urban units. Janković’s drawings are interpreted as a synthesis of artistic expression and documentary value, contributing to the preservation of the visual memory of old Priština.